Effects of Potential Detoxifying Agents on Growth Performance and Deoxynivalenol (DON) Urinary Balance Characteristics of Nursery Pigs Fed DON-Contaminated Wheat - H. L. Frobose; E. W. Stephenson; M. D. Tokach; J. M. DeRouchey; S. S. Dritz; R. D. Goodband; J. C. Woodworth; R. E. Musser (Kansas Agricultural Experiment Station Research Reports, 2015)
Two experiments were conducted to evaluate the effects of detoxifying agents on the growth performance of nursery pigs fed diets contaminated with deoxynivalenol (DON). Naturally DON-contaminated wheat (6 ppm) replaced noncontaminated wheat in diets to achieve desired dietary DON concentrations. Basal ingredients were tested for mycotoxin and amino acid content prior to diet manufacturing. Diets were pelleted at 180˚F with a 45-s conditioning time. A total of 238 barrows and gilts (PIC 327 × 1050; initially 29.6 ± 5.6 lb and 42 d of age) were used in a 21-d growth study. Pens of pigs were allotted by BW to 1 of 5 treatments in a completely randomized design with a 2 × 2 + 1 factorial arrangement. The 5 experimental diets included the following components, 1) positive control (PC;<0.5 mg/kg DON); 2) PC + 1.0% Product X (Nutriquest LLC, Mason City, IA); 3) negative control (NC; 4.0 mg/kg DON); 4) NC + 1.0% Product X; and 5) NC + 1.0% sodium metabisulfite (SMB; Samirian Chemicals, Campbell, CA). There were 6 or 7 replicate pens per treatment and 7 pigs per pen. Chemical analysis indicated a low level of fumonisin (<1 ppm) was present but that all DON concentrations matched calculated values. Analyzed DON concentrations were decreased by 92% when pelleted with SMB. Overall (d 0 to 21), a DON × Product X interaction was observed for ADG (P<0.05) and ADFI (P<0.10). Adding Product X to PC diets had no effect on ADG or ADFI; however, when added to NC diets, ADG, and ADFI became worse. As anticipated, DON reduced (P<0.001) ADG, ADFI, and F/G by 24, 16, and 10%, respectively. Deoxynivalenol-associated reductions in ADG were most distinct (50%) during the initial period (0.42 vs. 0.84 lb from d 0 to 7). Adding SMB to NC diets improved (P<0.01) ADG, ADFI, and F/G compared to pigs fed the NC alone, and also improved (P<0.02) ADG and F/G compared to pigs fed PC diets. A concurrent urinary balance experiment was conducted using diets 3 to 5 from Exp. 1 to evaluate Product X and SMB on DON urinary metabolism. A 10-d adaptation was followed by a 7-d collection using 24 barrows in a randomized complete block design. Pigs fed NC + SMB diet had greater urinary output (P<0.05) than pigs fed NC + Product X, with NC pigs intermediate. Daily DON excretion was lowest (P<0.05) in the NC + SMB pigs. However, as a percentage of daily DON intake, NC + SMB fed pigs excreted more DON than they consumed (164%), greater (P<0.001) than pigs fed the NC (59%) or NC + Product X (48%), and indicative of degradation of DON back to the parent DON molecule. Overall, Product X did not alleviate DON effects on growth nor did it reduce DON absorption and excretion. However, hydrothermally processing DON-contaminated diets with 1.0% SMB restored ADFI and improved F/G. Even so, the urinary balance experiment revealed that some of the converted DON-sulfonate could degrade back to DON under physiological conditions. While SMB appears promising to restore performance in pelleted DON-contaminated diets, additional research needs to address handling and long-term supplementation concerns and to evaluate the stability of the DON-sulfonate conversion.
Keywords: adsorbents; deoxynivalenol; mycotoxins; nursery pigs; sodium metabisulfite